Definition of the objective function optimizing the use of empty rail car fleet - Рибальченко, Лілія Ігорівна (Eastern-European Journal of Enterprise Technologies, 2012)
With the development of the transport market and competition, one of the major issues for the transportation system is the timely provision of required type cars all consignors according to their applications. Certain conditions are fulfilled complicated by the acute shortage of wagons and their poor condition. Options to address this issue is to improve technology services in transportation, which is possible in improving the quality of operational planning trainset of the Railways. In this paper apply the method of genetic algorithm for solving the problem of distribution of empty wagons at landfills directorates. For the operation of the genetic algorithm fitness function is formed and represented explicitly. In this case, this approach will analyze and take into account many factors that affect the distribution of empty wagons